BUSINESS FEASIBILITY ANALYSIS OF USING PALM OIL FLOUR AS A SUBSTITUTE INGREDIENT IN MAKING COOKIES - Silviani; Febriana Roosmawati; Tifany Zia Aznur; Adi Widjajanto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the feasibility of palm oil flour Cookies business as a local food product based on plantation resources. The study uses a quantitative descriptive method with a business feasibility analysis approach. Primary data were obtained through production trials, recording production costs, selling prices, and production capacity, while secondary data were obtained from various relevant literature. The analysis was carried out on market aspects using the Segmenting, Targeting, Positioning (STP) and market size (TAM, SAM, SOM) approaches, and financial aspects through investment calculations, production costs, cost of goods manufactured (COGS), revenue, profit, R/C Ratio, Break Even Point (BEP), Payback Period, Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (B/C Ratio), and sensitivity analysis. The results of the study indicate that the palm oil flour Cookies business is feasible to be developed. At a production capacity of 350 packages per month with a selling price of Rp17,000 per package, the business earns revenue of Rp5,950,000, production costs of Rp3,701,375, and a net profit of Rp2,248,625 per month. The R/C Ratio value is 1.61, BEP 217.73 packages, Payback Period 0.47 months, NPV Rp101,241,695, IRR 2,577.23%, and B/C Ratio 1.60. Sensitivity analysis shows that the business remains feasible in scenarios of changes in selling prices, production costs, and sales, so it has the potential to be developed as a local food business on a household or MSME scale.